Роль соціальних служб в процесі реабілітації та абілітації ветеранів в Україні - Процик, Оксана Степанівна; Protsyk, Oksana Stepanivna (Національний університет "Львівська політехніка", 2024)
Реабілітація та абілітація ветеранів є надзвичайно актуальними питаннями для сучасного українського суспільства, особливо в умовах повномасштабної війни. Ветерани після повернення з фронту стикаються з фізичними, психологічними та соціальними труднощами, які потребують комплексної підтримки [1]. Протягом тривалого часу процес адаптації учасників бойових дій не мав системного підходу, а соціальні послуги часто зводилися до матеріальної допомоги. З огляду на зростання кількості ветеранів, потреба у повноцінній підтримці є критичною [2]. Ефективна реабілітація впливає не лише на якість життя самих ветеранів, а й на благополуччя їхніх родин, рівень довіри до держави та загальну соціальну стабільність. Тому діяльність соціальних служб у цій сфері є важливою складовою державної політики [3]. Об’єкт дослідження: процес реабілітації та абілітації ветеранів в Україні. Предмет дослідження: роль соціальних служб у процесах абілітації та реабілітації ветеранів. Мета дослідження: визначення ролі соціальних служб у процесах абілітації та реабілітації ветеранів в Україні. Результати дослідження: У першому розділі розглянуто поняття соціальних послуг, підтримки, реабілітації та абілітації. У другому – проаналізовано нормативно-правову базу та актуальні програми допомоги ветеранам, а також досвід інших країн. У третьому – подано результати дослідження на прикладі Львівської області, зокрема Центру «Галичина» та Абілітаційного ХАБу. Виокремлено труднощі в організації допомоги як для ветеранів, так і для фахівців.

Rehabilitation and habilitation of veterans are extremely relevant issues for modern Ukrainian society, especially in conditions of full-scale war. Veterans after returning from the front face physical, psychological and social difficulties that require comprehensive support [1]. For a long time, the process of adaptation of combatants did not have a systematic approach, and social services were often reduced to material assistance. Given the growing number of veterans, the need for full support is critical [2]. Effective rehabilitation affects not only the quality of life of veterans themselves, but also the well-being of their families, the level of trust in the state and general social stability. Therefore, the activities of social services in this area are an important component of state policy [3]. Object of the study: the process of rehabilitation and habilitation of veterans in Ukraine. Subject of the study: the role of social services in the processes of habilitation and rehabilitation of veterans. Purpose of the study: determining the role of social services in the processes of habilitation and rehabilitation of veterans in Ukraine. Research results: The first section examines the concepts of social services, support, rehabilitation and habilitation. The second section analyzes the regulatory framework and current programs of assistance to veterans, as well as the experience of other countries. The third section presents the results of the study using the example of the Lviv region, in particular the Center "Halychyna" and the Habilitation Hub. Difficulties in organizing assistance for both veterans and specialists are highlighted.
Role of social services in the process of rehabilitation and habilitation of veterans in Ukraine
Keywords: 6.231.00.00; соціальна робота; реабілітація; абілітація; ветерани; social work; rehabilitation; habilitation; veterans. List of used literature sources. 1. Herman; O.; & Yanus; M. (2023). Psychological and social adaptation of victims of military conflicts and man-made disasters: problems and opportunities. Military conflicts and man-made disasters: historical and psychological consequences. 13-14. 2. Biskup; V. (2022). Habilitation as a process of restoring the ability to everyday life. Psychosocial resources of personal and social development in the era of globalization; 80–81. Ternopil: Western Ukrainian National University. 3. Zhyzherya; O.; & Vasilyeva; N. (2025). Peculiarities of social rehabilitation of combatants. Thematic area "innovative means and technologies of diagnostics; treatment and rehabilitation of different population groups". 164